Crude glycerin inclusion in Santa Inês ewes’ diet before and during the breeding season: its effects on physiological parameters, hematological variables, and reproductive performance - Almeida, Marta Maria Soares de Freitas (2020)
In this study, we aimed to evaluate the effect of concentrate supplementation containing crude glycerin (CG) before and during the breeding season on the physiological and blood biochemical variables as well as on the reproductive performance of Santa Inês ewes. A total of 24 ewes (12 pluriparous and 12 nulliparous ewes, 4 and 1.5 years old, weighing an average of 40 ± 5 and 27 ± 3 kg, respectively) were randomly assigned to three treatments consisting of different dietary concentrations of CG (0%, 5%, and 10 % of the total dry matter). The experiment lasted 63 days and was divided into three 21-day phases. In the first and second phases, the animals were subjected to flushing. In the second and third phases, we evaluated the animals’ reproductive performance. Weather, physiological, and blood biochemical variables were also studied. The results indicated that the inclusion of CG did not influence significantly (P > 0.05) either the ewes’ body weight or their body condition score. All ewes exhibited estrus during the breeding season. Their respiratory rate was significantly influenced by the time of day (P < 0.0001). A 10% CG supplementation did not drastically change the hematological and biochemical variables, which were within the reference ranges. However, the week of supplementation influenced serum metabolites (P < 0.05). Thus, these results indicate that CG could be used in up to 10% in replacement of ground corn without significantly affecting the physiological, hematological, and biochemical parameters of the ewes or their reproductive performance before and during the breeding season.